2019
DOI: 10.3329/aba.v23i2.50054
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Characterization and Evaluation of Nineteen Gladiolus Germplasm

Abstract: Nineteen gladiolus germplasms were characterized and evaluated in the Research Field of the Department of Horticulture, Bangabandhu Sheikh Mujibur Rahman Agricultural University, Gazipur, during November 2017 to May 2018 for identifying suitable line(s) to release as a variety for commercial cultivation. The accession G8 produced the highest number of shoots (3.3) and effective shoots (3.0) per hill. The accessions that produced flower stalk within 75 days of planting included BARI gladiolus- 3 (G1, 58.7 days)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 4 publications
1
7
0
Order By: Relevance
“…The average length of petals among accessions was 2.99 mm in Ms12 from M. spicata up to 5.23 mm in Ma24 from M. aquatica (Table 4). Hoque et al (2014) reported that the petal length ranged from 3 to 3.5 mm which has overlap with the data reported here. The phenotypic and genetic variation coefficients for this trait were 11.33 and 11.3%, respectively.…”
Section: Variation In Reproductive Traitssupporting
confidence: 89%
See 1 more Smart Citation
“…The average length of petals among accessions was 2.99 mm in Ms12 from M. spicata up to 5.23 mm in Ma24 from M. aquatica (Table 4). Hoque et al (2014) reported that the petal length ranged from 3 to 3.5 mm which has overlap with the data reported here. The phenotypic and genetic variation coefficients for this trait were 11.33 and 11.3%, respectively.…”
Section: Variation In Reproductive Traitssupporting
confidence: 89%
“…Petal color in Ms20 and Ms12 from M. spicata was white, in Ml30 and Ml29 both from M. longifolia, Ms22 from M. spicata and Ma24 from M. aquatica was violet, and was dark violet in Ml28 from M. longifolia. Hoque et al (2014) in the study of morphological traits in some germplasm of mint reported that the color of open flower was white and purple. Vining et al (2019) in genetic diversity survey of M. aquatica demonstrated that M. aquatica corollas were purple.…”
Section: Variation In Reproductive Traitsmentioning
confidence: 99%
“…Over the last couple of decades, there have been numerous phylogenetic studies of the genus Mentha, mostly of the section Mentha, using morphological, cytological and chemical characters (e.g., [59,62,63,[80][81][82][83][84][85][86][87][88][89][90][91]) as well as molecular markers (e.g., [55,60,61,64,66,[92][93][94][95][96][97][98][99][100][101][102][103][104][105]). However, despite the enormous amount of data gathered, the classic taxonomic divisions (e.g., [22,106]) still largely stand.…”
Section: Former Phylogenies In the Light Of New Resultsmentioning
confidence: 99%
“…This result was in agreement with the findings of Hossain et al (2011), who found number of leaf ranged from 8.50-12.25. Hoque et al (2019) found that number of leaf was varied significantly ranges from 11.7-8.0. Wide variation in leaf length amongst some genotypes of gladiolus was observed by Singh, and Dadlani (1990).…”
Section: Number Of Leaves Leaf Length and Leaf Breadthmentioning
confidence: 95%